Flank or front : an assessment of military-political developments in the High North - Nieminen, Tauno (War, 1991)
Finnish Defence Studies is published under the auspices of the War College, and the contributions reflect the fields of research and teaching of the College. Finnish Defence Studies will occasionally feature documentation on Finnish Security Policy. Views expressed are those of the authors and do not necessarily imply endorsement by the War College.